Temporal/compartmental changes in viral RNA and neuronal injury in a primate model of NeuroAIDS - González, R. Gilberto (PLoS One, 2018)
Despite the advent of highly active anti-retroviral therapy HIV-associated neurocognitive disorders (HAND) continue to be a significant problem. Furthermore, the precise pathogenesis of this neurodegeneration is still unclear. The objective of this study was to examine the relationship between infection by the simian immunodeficiency virus (SIV) and neuronal injury in the rhesus macaque using in vivo and postmortem sampling techniques. The effect of SIV infection in 23 adult rhesus macaques was investigated using an accelerated NeuroAIDS model. Disease progression was modulated either with combination anti-retroviral therapy (cART, 4 animals) or minocycline (7 animals). Twelve animals remained untreated. Viral loads were monitored in the blood and cerebral spinal fluid, as were levels of activated monocytes in the blood. Neuronal injury was monitored in vivo using magnetic resonance spectroscopy. Viral RNA was quantified in brain tissue of each animal postmortem using reverse transcription polymerase chain reaction (RT-PCR), and neuronal injury was assessed by immunohistochemistry. Without treatment, viral RNA in plasma, cerebral spinal fluid, and brain tissue appears to reach a plateau. Neuronal injury was highly correlated both to plasma viral levels and a subset of infected/activated monocytes (CD14+CD16+), which are known to traffic the virus into the brain. Treatment with either cART or minocycline decreased brain viral levels and partially reversed alterations in in vivo and immunohistochemical markers for neuronal injury. These findings suggest there is significant turnover of replicating virus within the brain and the severity of neuronal injury is directly related to the brain viral load.